New vane type wind turbine of high efficiency - Usubamatov, Ryspek, Prof. Dr. (Federation of Engineering Institution of Islamic Countries, 2012)
World Engineering Congress 2010 was jointly organized by Federation of Engineering Institutions of Islamic Countries, Malaysian Society for Engineering & Technology, and Universiti Putra Malaysia (UPM), 2nd - 5th August 2010 was held at Hilton Hotel, Riverside Majestic Hotel and Grand Margherita Hotel Kuching, Sarawak, Malaysia.